Non-functional neuroendocrine tumor with multisystemic metastasis in a cat - Baeta, Silvia A.F.; Abreu, Douglas M.; Sousa, José Arthur C.; Farias, Ingrid S.; Sá, Isael S.; Silva, Silvana Maria M.S.; Serakides, Rogéria; Ocarino, Natalia M. (Brazilian Journal of Veterinary Pathology, 2021)
An eight-year-old castrated female feline was referred for necropsy with a history of apathy, inappetence, abdominal distension, hypersensitivity to abdominal palpation, and evidence of abdominal neoplasms on ultrasound. Macroscopically, multifocal to coalescent, yellowish-white, firm and infiltrative nodules were observed on the surface of the parietal peritonium and in abdominal and thoracic organs. Microscopic characteristics of the neoplasm suggested a neuroendocrine origin, but did not allow a definitive diagnosis and determination of the origin. Immunohistochemistry revealed that neoplastic cells expressed vimentin, CD56, neuron specific enolase, and PGP 9.5 and were negative for biogenic amines and hormonal peptides. Based on anatomopathological and immunohistochemical findings, diagnosis of metastatic non-functional neuroendocrine tumor was confirmed.